Analysis of Language Learning Strategies Used by Two Groups of Students of Differing Age Range (2017)
This short exploratory study aims to analyze the language learning strategies used by part of two groups of students with different age range in seventh and eleventh grade. The instruments used to carry out this study were: an adapted questionnaire to identify Language Learning Strategies (LLS), a focus group discussion, and an interview. The results show that age is an important factor when determining LLS. However, it was also found that there are other variables such as task nature, course methodology, and parents’ availability, among others, that may influence strategy choice.